IMPLEMENTASI NILAI PANCASILA SEBAGAI LANDASAN PENGEMBANGAN KEBUTUHAN PANGAN DI INDONESIA - Ummi, Syafwatul (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2024)
Pancasila as the state ideology is a foundation in all things to realize and direct various development sectors. Various existing sectors must of course be linked to Pancasila, including the food sector. The development of food innovation in advancing food security must be in accordance with the principles of Pancasila in order to realize food security that is fair, sustainable, and oriented towards the welfare of all Indonesian people. The first principle of Pancasila is the basic reference in managing food in accordance with the mandate of God Almighty. The second principle of Pancasila as a driver for the desire to develop food innovation by ensuring fair and civilized contributions. The third principle emphasizes the importance of collaboration between the government and society in realizing Indonesian food innovation. The fourth principle emphasizes the principle of deliberation in building community participation in realizing food innovation, and the fifth principle emphasizes the principle that food must be able to meet the basic needs of all Indonesian citizens. This article aims to provide the implementation of Pancasila in carrying out the practice of developing food innovation in Indonesia and describe the challenges of food security based on Pancasila as the state ideology